PENGARUH EDUKASI KESEHATAN DAN AGAMA ISLAM TERHADAP PENGETAHUAN PENGGUNAAN VAKSIN COVID-19 - Ahmad J; Nurul Fadhila Gani; Dirhamzah Dirhamzah; Titi Mildawati (IAI Al-Mawaddah Warrahmah Kolaka, 2023)
The way that can be done to overcome the pandemic and decrease the rate of people in sufferers of COVID-19 is by administering vaccines. Knowledge about the use of vaccines in religion and the health sector may influence public acceptance of vaccines. This study aims to determine the effect of health and religious education on the use of the covid-19 vaccine. This study used a quantitative approach with a quasi-experimental method, with a sample size of 30 respondents, conducted in a School in Gowa Regency, South Sulawesi Province. The result showed most of the respondents is female (83%), Based on the paired t-test, a p-value of 0.000 was obtained, meaning that there was an effect of health and religious education on increasing knowledge about COVID-19 vaccination. The conclusion from this study is that education is needed to increase the knowledge of the Covid-19 vaccine. Attitude and variablel variables may need to be studied for further research